Pengembangan Bahan Ajar Mata Kuliah Bahasa Indonesia S 2 Semester Satu Pendidikan Dasar Fkip Univ ersitas Bengkulu T.A. 2020/2021 - Daimun Hambali Hambali (Universitas Bengkulu, 2021)
The purpose of this research is to (a) develop teaching materials for Indonesian language courses for Master of Elementary Education (Dikdas) students, (b) to create Indonesian language lecture materials that support students' abilities as candidates for Masters in Basic Education, (c) availability of references Indonesian language material that can be used by students in lectures and the completion of their final project (thesis), and (d) the availability of various references to Indonesian subjects. In addition, the teaching materials for this Indonesian Language Course can be used for research activities; (a) increasing the literacy competence of teaching staff in the Primary Education Study Program, (b) increasing the quality of Indonesian language course material content, and (c) increasing libraries in the S-2 Dikdas Study Program, in improving the quality of lectures and student learning outcomes. This study was designed using a Research and Development approach. Research data collection techniques; interviews and documentation. Data analysis using qualitative analysis. The research output is expected to be; (a) a draft of Indonesian Language Course teaching materials for Master of Basic Education students, and (b) the results of the research will be published in the S-2 Basic Education journal, (c) a printed reference book, and (d) obtain an IPR.